2016
DOI: 10.1140/epjd/e2016-70016-x
|View full text |Cite|
|
Sign up to set email alerts
|

Exact dynamics of two ultra-cold bosons confined in a one-dimensional double-well potential

Abstract: Abstract. The dynamics of two ultra-cold bosons confined in a one-dimensional double-well potential is studied. We compare the exact dynamics governed by a full two-body Hamiltonian with the dynamics obtained in a two-mode model approximation. We show that for sufficiently large interactions the twomode model breaks down and higher single-particle states have to be taken into account to describe the dynamical properties of the system correctly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Different methods have been employed to tackle the many-body problem of bosons in a double-well, even outside the mean-field regime [43][44][45][46][47]. Addressing the subject from a few-body perspective [48][49][50][51][52], however, might lead to new insight on the properties of these systems. Here we show that, in the regime where the repulsion between the impurity and the background is dominant, the system can exhibit non-trivial dynamical effects: the impurity undergoes Josephson-like oscillations when initialized at the edge of the system, and can have its tunneling enhanced when a barrier is present.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been employed to tackle the many-body problem of bosons in a double-well, even outside the mean-field regime [43][44][45][46][47]. Addressing the subject from a few-body perspective [48][49][50][51][52], however, might lead to new insight on the properties of these systems. Here we show that, in the regime where the repulsion between the impurity and the background is dominant, the system can exhibit non-trivial dynamical effects: the impurity undergoes Josephson-like oscillations when initialized at the edge of the system, and can have its tunneling enhanced when a barrier is present.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for ultracold quantum gases, the most relevant set-up includes a parabolic trap, which is not analytically solvable for the whole range of interactions by the Bethe ansatz. Before studying the parabolic trap case in detail, let us briefly mention that many works have studied the TG gas in different external trapping potentials, a non-comprehensive list includes potentials such as split traps [113][114][115][116][117][118], optical lattices [119,120], hard wall boxes [121][122][123][124], ring potentials [125], double wells [86,[126][127][128][129][130][131][132][133][134][135], and anharmonic potentials [136]. The experimental realization of a TG gas was first reported in [5,6].…”
Section: Tonks-girardeau Gas In a Parabolic Trapmentioning
confidence: 99%
“…It is distinct from the truncation of a high-lying band of states in electronic systems that features a spectral gap. Even few-particle systems impose severe limitations [36], while in this work we have considered a many-body system (N 1) with no gap (Fig.3a). Using a semiclassical perspective, we have shown that the emergence of chaos requires one to forego the naive reasoning.…”
Section: √Xmentioning
confidence: 99%